Muscle strength but not functional capacity is associated with plasma interleukin-6 levels of community-dwelling elderly women - Oliveira,D.M.G. (2008)
The association of plasma interleukin-6 (IL-6) levels, muscle strength and functional capacity was investigated in a cross-sectional study of community-dwelling elderly women from Belo Horizonte, Brazil. Elderly people who present controlled chronic diseases with no negative impact on physical, psychosocial and mental functionality are considered to be community-dwelling. Psychological and social stress due to unsuccessfully aging can represent a risk for immune system disfunctions. IL-6 levels, isokinetic muscle strength of knee flexion/extension, and functional tests to determine time required to rise from a chair and gait velocity were measured in 57 participants (71.21 ± 7.38 years). Serum levels of IL-6 were measured in duplicate and were performed within one single assay (mouse monoclonal antibody against IL-6; High-Sensitivity, Quantikine®, R & D Systems, USA; intra-assay coefficient of variance = 6.9-7.4%; interassay coefficient of variance = 9.6-6.5%; sensitivity = 0.016-0.110 pg/mL; mean = 0.039 pg/mL). Muscle strength was assessed with the isokinetic dynamometer Biodex System 3 Pro®. After the Shapiro-Wilk normality test was applied, correlations were investigated using Spearman and Kruskal-Wallis tests. Post hoc analysis was performed using the Dunn test. A significant negative correlation was observed between plasma IL-6 levels (1.95 ± 1.77 pg/mL) and muscle strength for knee flexion (70.70 ± 21.14%; r = -0.265; P = 0.047) and extension (271.84 ± 67.85%; r = -0.315; P = 0.017). No significant correlation was observed between IL-6 levels and the functional tests (time to rise from a chair = 14.65 ± 2.82 s and gait velocity = 0.95 ± 0.14 m/s). These results suggest that IL-6 is associated with reduced muscle strength.